Study on mechanical behavior of Q690D high strength steel bearing-type bolted connections. (February 2020) - Guo, Hongchao; Xie, Yong; Liu, Yunhe; Yang, Dixiong
Abstract: The failure modes and ultimate bearing capacities of Q690 high strength bolted joints under different bolt arrangement were compared and analyzed through static tension test and finite element simulation. Then the influences of different bolt end pitch, edge pitch, pitch, bolt strength grade and bolt diameter were discussed with theoretical calculation and the applicability of EC3 and other standards were investigated. The results show that when the bolts were transversely arranged, the major failure modes of the specimens were pre-hole thrust failures, the stress of the connecting plate distributed symmetrically along the middle line of the bolt hole spacing, and the ultimate bearing capacities increased significantly with the increase of the bolt end distance, edge distance and bolt pitch in a certain range. According to Eurocode 3, the bearing capacities of the connection joints predicted by the deformation of bolt hole presented a large deviation. When the bolts were arranged longitudinally, the end bolts were subjected to large forces, and the net cross-sectional failures occurred in all specimens. The effect of edge distance on the bearing capacity was significant, while the change amplitudes of specimens with end distance and bolt pitch on the bearing capacities were little. Eurocode 3 was applicable to the calculation of the bearing capacity of the joint. The increase of bolt strength grade can improve the static friction forces between plates, and the increase in bolt diameter can improve the bearing capacity of the joint significantly.